Study on the Effect of Popular Culture on Digital Game Motivation - Editor, Mert Erkan; Kerem Yıldırım Şimşek,; Eyüp Furkan Gümüş, (Journal of Educational Issues, 2024)
In parallel with the constantly developing and changing technology, there is an increase in the consumption of digital games and a change in the way of use. About 30 million people in Turkey are interested in digital games and spend their free time in this way. Considering the Z generation, a significant portion of these users are high school and university students. There are even high school and university students who continue their professional careers as e-athletes. Determining why the Z generation prefers digital games and sports as a career or an important tool to evaluate their spare time can contribute to the e-sports literature. In this context, the aim of the research is to understand the motivations of generation Z to play digital games and to contribute to the e-sports literature. In the research, 335 digital game users were reached on the internet with the convenience sampling technique. In obtaining the data; Demir and Hazar (2018); Digital game playing motivation scale developed by the company was used. In the analysis of the data, the scale dimensions were compared according to the demographic characteristics of the sample (gender, education, age and income, daily and annual playing times) using variance analysis and significant differences were determined. As a result of the analysis, it has been determined that men have a higher motivation to play digital games than women, those with a high school education level are more motivated to play digital games than those with a university education level, and there is no significant difference in the motivation of playing digital games in the age group from other age groups. As a result, the motivations of the Z generation to play digital games were examined and suggestions were made to the e-sports industry and literature as a result of the differences in demographic characteristics. However, much more can be done to help us understand the underlying psychological processes involved in the motivation of young players, particularly in terms of passion and flow experiences.